L‟image du Japon et de la culture japonaise dans le roman« Stupeur et Tremblements » - BENYESSAAD Mebrouk , TITRAOUI Oussama (كلية الاداب و اللغات, 2026)
Our research is entitled: “the image of Japan in Stupor and tremors, novel and movie , his adaptation to cinema” will focus on the imagological study of Amélie‟s novel and Alain Corneau‟s movie. In order to respond to our problem surrounding the representation of Japan, we call on other autobiographical, structural, semiotic, narratological, comparative and analytical approaches.
d‟Amélie Nothomb et son adaptation au cinéma par Alain Corneau
Keywords: Mots clés : image -japon - imagologie - stupeur et tremblements –film –roman-adaptation.